SUPERVISI KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MTS MINHAJULHAQ KABUPATEN PURWAKARTA TAHUN PELAJARAN 2023/2024 - Sutra, Ona; Sayyi, Ahmad; Rofi’i, Ahmad (UNISAN JURNAL, 2025)
The implementation of supervision in educational institutions is a strategic effort to enhance the quality of human resources. Schools serve as one of the primary facilities, with teachers being essential elements in human resource development. Supervision is necessary to monitor, evaluate, and improve the quality of the teaching and learning process conducted by teachers. Furthermore, supervision activities are expected to shape teachers' mindsets, fostering strong commitment so they can perform their duties and responsibilities professionally. This study focuses on the following aspects: 1) The implementation of the principal's academic supervision in improving teacher performance, 2) The results of the principal's academic supervision in improving teacher performance, 3)The factors influencing the effectiveness of the principal's academic supervision in improving teacher performance. This research employs a qualitative approach, specifically field research. Data collection techniques include observation, interviews, and documentation. The data analysis process consists of three stages: data reduction, data presentation, and conclusion drawing. The findings of this study reveal the following: 1) The implementation of the principal's academic supervision involves direct classroom visits and occasionally observing the learning process from outside the classroom. 2) The results of academic supervision by the principal of Mts Minhajulhaq have yielded positive outcomes, such as improvements in teaching preparation (teaching materials), achieving curriculum implementation goals within specified periods, and increased teacher engagement in their duties. 3) Factors influencing the effectiveness of the principal's supervision are categorized into two: internal factors, such as punctuality issues, and external factors, such as the school’s environment and conditions